2022
DOI: 10.21203/rs.3.rs-1280929/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence, Parents’ Hesitancy, and Determinants of COVID-19 Vaccination Among Children: A Multi-Country Study From the Eastern Mediterranean Region

Abstract: Background: Huge efforts are being made to control the spread and impacts of the coronavirus pandemic using vaccines. However, willingness to be vaccinated depends on factors beyond the availability of vaccines. The aim of this study was three-folded: to assess the prevalence of children’s vaccination against COVID-19, to explore parents’ attitudes towards children’s vaccination, and to discover the factors associated with parents’ hesitancy towards children’s vaccination in several countries in the Eastern Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The fact that most children have the disease with mild symptoms and are not severely affected by it creates the perception that they do not need to be vaccinated. In addition, the closure of schools during the pandemic period may have reduced the risk of disease in children, which may have created the perception that the risk status of children is low and that there is no need for vaccination ( Gendler & Ofri, 2021 ; Khatatbeh et al, 2022 ). In our study, 31% of the parents reported that their children over the age of 12 had had the COVID-19 vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that most children have the disease with mild symptoms and are not severely affected by it creates the perception that they do not need to be vaccinated. In addition, the closure of schools during the pandemic period may have reduced the risk of disease in children, which may have created the perception that the risk status of children is low and that there is no need for vaccination ( Gendler & Ofri, 2021 ; Khatatbeh et al, 2022 ). In our study, 31% of the parents reported that their children over the age of 12 had had the COVID-19 vaccine.…”
Section: Discussionmentioning
confidence: 99%